Takhrij and Syarah Hadith of Agrotechnology Utilization of Empty Land - Adetia Nurfarida; Wahyudin Darmalaksana; Yeni Huriani; Budy Frasetya TQ (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith regarding vacant land. This research method is a qualitative type through literature and field studies with the takhrij and sharah hadith approaches. The result and discussion of this research is that the use of vacant land which has no owner has the right to be planted by anyone because it is a recommendation from Rasullah Saw. The conclusion of this research is the takhrij and syarah of the Prophet SAW regarding the use of empty land that must be planted by anyone, even though many people oppose it, but it still has to be planted so that there is no empty land anywhere.